2006
DOI: 10.1021/jp065406y
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Bilayer Free Volume Analysis Employing the Thermal Ring-Closing Reaction of Merocyanine Molecular Switches

Abstract: The free volume properties of phospholipid bilayers have been determined using a new assay that applies the photochromic and solvatochromic properties of merocyanines. The orientation and embedding depth of the merocyanines in the bilayer are controlled using substitution on the merocyanine indole moiety. The free volume changes at the aqueous interface (region 1), the phospholipid headgroup (region 2), and the aliphatic interior (region 3) of the bilayer are compared by analyzing the rate constants for the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Permeation via these hydrated defects allows protons to avoid the high-energy barrier associated with partitioning into the hydrophobic membrane interior, which is commonly described as the solubility-diffusion mechanism. 45 The smallest free volume was found in the phospholipid head group region, while the largest free volume was detected in the interior aliphatic region. 13,14,43 The stability of the lipid systems can also be interpreted from the extent of ion permeation.…”
Section: Ion Permeation Studies In Lipid Vesiclesmentioning
confidence: 92%
“…Permeation via these hydrated defects allows protons to avoid the high-energy barrier associated with partitioning into the hydrophobic membrane interior, which is commonly described as the solubility-diffusion mechanism. 45 The smallest free volume was found in the phospholipid head group region, while the largest free volume was detected in the interior aliphatic region. 13,14,43 The stability of the lipid systems can also be interpreted from the extent of ion permeation.…”
Section: Ion Permeation Studies In Lipid Vesiclesmentioning
confidence: 92%
“…The strength of the interchain forces controls the formation or otherwise of voids, packing defects within the hydrophobic core of the membrane [ 23 ], and it is suggested that these control the depth to which raclopride partitions into the membrane. For the reaction to progress, the free proton carried by the CAD must be in close proximity to the ester moieties of the lipid membrane: here, we propose that these voids promote the migration of the CAD towards the hydrophobic centre of the membrane, into a region where they are effectively sequestered and passivated.…”
Section: Resultsmentioning
confidence: 99%
“…As soon as the UV is turned on, SP converts into its photoisomer known as 대한금속 • 재료학회지 제59권 제5호 (2021년 5월) merocyanine (MC). The formed MC is zwitter-ionic and hydrophilic in nature, causing the interaction with the head groups of lecithin [33,38,39] Experiments were conducted to determine whether SAO and PRF were complementary, and whether it could be used instead of ZnS:Cu, given its certain benefits over ZnS:Cu.…”
Section: Experiments Proceduresmentioning
confidence: 99%